Microplastics in Table Salts: Sources, Abundance, Types, and Consumption– A Review - Fatima Kanwal; Zafar Iqbal Shams (Pakistan Journal of Analytical & Environmental Chemistry, 2025)
Microplastics (MPs) exist everywhere, from the bottom of the ocean to the peak of mountains, and pose a significant threat to species and habitats. These tiny plastic particles have polluted all components of the biosphere, including both biotic and abiotic components of the Earth. There is a global concern regarding this problem and studying MPs in various compartments of Earth is mandatory. This paper reviews the research articles published worldwide on microplastic particles' prevalence, composition, abundance, color, and structure using methodologies like filtration, spectroscopy, and chemical analysis in all table salts, including sea, rock, and lake salts. This review paper analyzes and compares the Atlantic Ocean as the most polluted with per capita plastic waste disposal compared to the Arctic and Pacific oceans. Microplastic contamination is higher in Asia. The most contaminated salt type is sea salts followed by lake and rock salts. Morphologically, fibers are more abundant than fragments or films of plastics. The consumption of table salts is higher in some countries, indicating the varying microplastic consumption in humans.